Endoscopic Management of Penetrated Adjustable Gastric Band with Its Connecting Tube: Report of a Case - COSKUN, HALİL; COŞKUN, HALIL; Bozkurt, SÜLEYMAN; BOZKURT, SÜLEYMAN; ATAK, Tuba; Kadioglu, HÜSEYİN; KADIOĞLU, HÜSEYİN (My University, 2011)
Aim: Laparoscopic adjustable gastric banding (LAGB) is a widely performed surgical procedure for the treatment of morbid obesity. Late complications mainly originate from either the injection port or the gastric band. Complications from the tube and band together are also described. Case Report: We here report a case of adjustable gastric band migrated subserosally into the stomach with its whole connecting tube, which was removed endoscopically using a band cutter. Conclusion: In selected patients endoscopic techniques in combination with minimally invasive procedures can safely be used in the treatment of complete gastric band migration.
Keywords: Endoscopy